Stigma toward Wuhan people during the COVID-19 epidemic: an exploratory study based on social media - Yazheng Di; Ang Li; He Li; Peijing Wu; Simin Yang; Meng Zhu; Tingshao Zhu; Xiaoqian Liu (BMC, 2021)
Abstract Background Stigma associated with infectious diseases is common and causes various negative effects on stigmatized people. With Wuhan as the center of the COVID-19 outbreak in China, its people were likely to be the target of stigmatization. To evaluate the severity of stigmatization toward Wuhan people and provide necessary information for stigma mitigation, this study aimed to identify the stigmatizing attitudes toward Wuhan people and trace their changes as COVID-19 progresses in China by analyzing related posts on social media. Methods We collected 19,780 Weibo posts containing the keyword 'Wuhan people' and performed a content analysis to identify stigmatizing attitudes in the posts. Then, we divided our observation time into three periods and performed repeated-measures ANOVA to compare the differences in attitudes during the three periods. Results The results showed that stigma was mild, with 2.46% of related posts being stigmatizing. The percentages of stigmatizing posts differed significantly during the three periods. The percentages of 'Infectious' posts and 'Stupid' posts were significantly different for the three periods. The percentage of 'Irresponsible' posts was not significantly different for the three periods. After government interventions, stigma did not decrease significantly, and stigma with the 'Infectious' attitude even increased. It was not until the government interventions took effect that stigma significantly reduced. Conclusions This study found that stigma toward Wuhan people included diverse attitudes and changed at different periods. After government interventions but before they took effect, stigma with the 'Infectious' attitude increased. After government interventions took effect, general stigma and stigmas with 'Infectious' and 'Stupid' attitudes decreased. This study constituted an important endeavor to understand the stigma toward Wuhan people in China during the COVID-19 epidemic. Implications for stigma reduction and improvement of the public's perception during different periods of epidemic control are discussed.